Axial Flux Motor with High Temperature Superconducting Tape Rotor and Variable Winding Configurations - Pinto, João Pedro Pereira (2022)
In order to empower the electrification of the aircraft sector, electrical machines and power systems need to be more efficient and have higher power and energy densities. Dis- covered approximately 100 years ago, superconductivity can play a key role in this matter and help in the transition to More Electric Airplane (MEA). Current studies are showing and proving the feasibility of applying superconductivity technology to power systems. In this thesis, a theoretical study of the underlying subjects and a practical analysis is made to an Axial Flux Inside Rotor Topology (AFIR) motor with an High Temperature Su- perconductor (HTS) and the capability of changing its poles and phases. The purpose of the study is to gain a more understanding knowledge about this motor topology, to inves- tigate its regeneration mode characteristics and its applicability in regenerative braking of MEAs which can operate with this type of machine. With both qualitative and quanti- tative analyses, this thesis approach is based on describing the motor characteristics and comprehending its behaviour. The results shown indicate the feasibility of this motor topology, the ability to change the number of poles while remagnetizing magnetic flux on the superconducting rotor and the possibility of regenerative braking.